Methylation and expression of RECK, P53 and RUNX genes in patients with esophageal cancer - Lu, Yanrong (Oncol Lett, 2017)
The methylation and expression of RECK, P53 and RUNX genes in patients with esophageal cancer was investigated. In order to achieve this aim, a sample of 58 patients with esophageal cancer, treated between February 2013 and February 2014, were considered as the observation group. Additionally, a sample of 42 healthy individuals was selected as the control group. Methylation status of RECK, P53 and RUNX genes from the observation and control groups were detected by MSP. Reverse transcriptase-quantitative PCR (RT-qPCR), enzyme-linked immunosorbent assay (ELISA), western blot and immunohistochemistry were used to detect the mRNA and protein levels of RECK, P53 and RUNX in both the observation and the control groups. Results showed that the methylation rates of RECK, P53 and RUNX genes in patients with esophageal cancer were 72.4% (42/58), 1.7% (1/58) and 3.4% (2/58), respectively, which were significantly different from those in the control group [7.1% (3/42), 90.5 (38/42), and 83.3% (35/42), respectively]. The mRNA expression level of RECK is only equal to the 2.3% of that in the control group, while the mRNA expression levels of P53 and RUNX were 65.1 and 47.2 times higher than those in the control group, respectively (p<0.05). ELISA showed that RECK protein level in the observation group (0.12±0.05) µg/l, was significantly lower than the control group (3.46±0.08) µg/l (p<0.05), while, P53 and RUNX protein levels in observation group were significantly higher than that in healthy people (6.43±0.12 µg/l vs. 0.64±0.06 µg/l and 4.32±0.14 µg/l vs. 0.53±0.09 µg/l, respectively), and the results were similar to western blot. The data of immunohistochemistry showed that the proportion of RECK protein positive cells in the observation group was significantly lower than that in the control group (9.5 vs. 82.3%, P<0.05), while the proportions of P53 and RUNX protein positive cell in the observation group were significantly higher than those in the control group (78.4 vs. 11.1% and 87.3 vs. 9.06%), respectively, (P<0.05). This study concluded that, in patients with esophageal cancer, the methylation of RECK gene is increased and the expression of RECK gene is inhibited, while methylation of RUNX gene decreased and their expression was increased. This change in methylation of these genes may promote the occurrence and development of esophageal cancer.